2012
DOI: 10.26719/2012.18.6.550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air pollution on onset of acute coronary syndrome in susceptible subgroups

Abstract: While long-term exposure to air pollutants is associated with an increase in heart diseases and mortality, little information is available about the short-term effects of air pollution. This case-crossover study assessed the relationship of particulate matter (PM 10 ) and carbon monoxide (CO) levels with hospital admission for acute coronary syndrome in Tehran, Islamic Republic of Iran. We interviewed 250 patients with a first episode of acute coronary syndrome and obtained data from hospital records and Tehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To evaluate the short-term effects of air pollution exposure, some studies took into account different lag patterns using single-day lags from lag 0 to 7 days. 6,9,22 Other studies have used both single-day lag and cumulative lag pattern. 7,8 Nevertheless, most of the included studies use a singleday lag pattern.…”
Section: Quantitative Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the short-term effects of air pollution exposure, some studies took into account different lag patterns using single-day lags from lag 0 to 7 days. 6,9,22 Other studies have used both single-day lag and cumulative lag pattern. 7,8 Nevertheless, most of the included studies use a singleday lag pattern.…”
Section: Quantitative Data Synthesismentioning
confidence: 99%
“…4,6,7,9,10,12,21,22,[24][25][26] The air pollutant concentrations were selected from the monitoring station nearest to the individual's residence or were calculated using the average concentrations in a region where there were >1 monitoring stations. Four studies assessed the air pollution exposure using complex dispersion models or land use regression models that included various databases, including traffic, meteorology, roadway geometry, vehicle emission, air quality monitoring data, and land use.…”
Section: Assessment Of Air Pollution Exposure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a significant correlation between CO and particulate matter of median aerometric diameter \10 lm (PM 10 ) concentrations with hospital admissions for cardiovascular disease was reported from Kermanshah Province in the western part of Iran (Khamutian et al 2014). In another study, a significant association was reported between the risks of acute coronary syndrome and elevated concentrations of CO in Tehran (Qorbani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, conditional or mixed model logistic regressions, accounting for correlation between case and control records, are commonly used to model the relation between air pollution and meteorological data with adverse health effects (Chan and Ng 2011;Chang et al 2005;Chen et al 2010;Gleason et al 2014;Guo et al 2009;Hansen et al 2012;Kan and Chen 2003;Lee et al 2008;Li et al 2011;Lin et al 2013;Qorbani et al 2012;Tobías et al 2011;Villeneuve et al 2012;Wendt et al 2014;Wong et al 2014;Yang et al 2004). However, the artificial neural networks (ANNs) were also used for modeling in the present study.…”
Section: Introductionmentioning
confidence: 99%